2008
DOI: 10.1787/budget-v8-art8-en
|View full text |Cite
|
Sign up to set email alerts
|

Budgeting in Estonia

Abstract: Since independence, Estonia has been at the forefront of institutional reform in the area of financial management. Budget formulation is divided into two distinct stages: strategic planning and preparation of the annual budget that is submitted to Parliament. This article describes key characteristics of budgeting in Estonia, including the development of the State Budget Strategy, the parliamentary process, the organisation of budget execution, and systems for accounting and auditing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…19 Bergvall et al's (2006) detailed account of Hungarian budget process reports that the t À 1 budget is usually amended at least once during the fiscal year. Similar conclusions are reached by Kraan et al (2008) for Estonia and Ruffner et al (2005) for Romania. 20 See Appendix A for details of unit-root tests.…”
Section: Estimation Methodologysupporting
confidence: 80%
“…19 Bergvall et al's (2006) detailed account of Hungarian budget process reports that the t À 1 budget is usually amended at least once during the fiscal year. Similar conclusions are reached by Kraan et al (2008) for Estonia and Ruffner et al (2005) for Romania. 20 See Appendix A for details of unit-root tests.…”
Section: Estimation Methodologysupporting
confidence: 80%
“…Although some studies (Kraan et al 2008; OECD 2011) have explored the role of PI in the executive phase of the budget process (and shown that the MoF does not pay significant attention to PI in budget negotiations), there are no studies that would have examined the use (or non‐use) of PI by legislators in Estonia. In order to get an overview of utilization of PI in the legislative budget process in Estonia, semi‐structured interviews were conducted with 9 (out of 11) legislators who were members of the finance committee in the 11th Estonian parliament (which was in session between 2007 and 2011).…”
Section: Use Of Pi In Legislative Budgeting In Estoniamentioning
confidence: 99%
“…Although this study focuses on the use of PI by legislators – in order to get an in‐depth picture of the role of PI in the legislative phase of the budget process – it is worth mentioning that for a related (but separate) study, the author interviewed five leading officials from the MoF, who are responsible for putting together the budget. They all admitted that in the course of the budget process, very limited attention is paid to PI (hence reinforcing the finding of OECD (2011) and Kraan et al (2008)), mostly because of time‐constraints and lack of analytical capacity, but also because of the ‘political’ nature of budgeting. Currently, the National Audit Office of Estonia is conducting an audit that examines the use of PI on the ministry level.…”
Section: Use Of Pi In Legislative Budgeting In Estoniamentioning
confidence: 99%
“…For a more detailed reviews of budgeting in Estonia, see Kraan, Wehner, and Richter (), Raudla (, , Forthcoming‐a), and Raudla and Kattel ().…”
mentioning
confidence: 99%
“…For a detailed discussion of the PBB aspects in the current Estonian system, see Kraan, Wehner, and Richter () and Raudla (Forthcoming‐b). …”
mentioning
confidence: 99%